menu
QAmmunity.org
Login
Register
My account
Edit my Profile
Private messages
My favorites
Register
Ask a Question
Questions
Unanswered
Tags
Categories
Ask a Question
3x - 4y = 7 3x + 2y = -5 When the second equation is subtracted from the first, the resulting equation is _____.
asked
Mar 24, 2017
194k
views
2
votes
3x - 4y = 7
3x + 2y = -5
When the second equation is subtracted from the first, the resulting equation is _____.
Mathematics
high-school
David Gausmann
asked
by
David Gausmann
8.1k
points
answer
comment
share this
share
0 Comments
Please
log in
or
register
to add a comment.
Please
log in
or
register
to answer this question.
2
Answers
4
votes
3x - 4y = 7
-(3x + 2y = -5)
= 0 - 6y = 12
-6y = 12
y = -2
The resulting equation would be y = -2.
Slugslog
answered
Mar 24, 2017
by
Slugslog
6.8k
points
ask related question
comment
share this
0 Comments
Please
log in
or
register
to add a comment.
4
votes
Answer:
the answer is -6y =12
Explanation:
Sufiyan Ghori
answered
Mar 29, 2017
by
Sufiyan Ghori
8.1k
points
ask related question
comment
share this
0 Comments
Please
log in
or
register
to add a comment.
Ask a Question
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.
8.3m
questions
10.9m
answers
Other Questions
How do you can you solve this problem 37 + y = 87; y =
What is .725 as a fraction
How do you estimate of 4 5/8 X 1/3
i have a field 60m long and 110 wide going to be paved i ordered 660000000cm cubed of cement how thick must the cement be to cover field
Write words to match the expression. 24- ( 6+3)
Twitter
WhatsApp
Facebook
Reddit
LinkedIn
Email
Link Copied!
Copy
Search QAmmunity.org